Functional analysis of recombinant channels in host cells using a fast agonist application system - Rozov, Andrei; Jappy, David (NMDA Receptors, 2017)
A reduced recombinant system provides a unique opportunity to study the biophysical properties of NMDAR channels with known subunit compositions, by using a point mutation approach to analyze the structural determinants of receptor function (Wollmuth and Sobolevsky, Trends Neurosci 27:321-328, 2004). However, in addition to the well-developed repertoire of molecular biological techniques, these types of studies also require electrophysiological methods that allow a wide range of receptor activation protocols that can adequately assess desensitization, inactivation, ion permeability, and other properties of the channels. Currently, one of the most well-developed techniques suitable for addressing these issues is use of the fast agonist application system for rapid activation of ligand gated ion-channels (Colquhoun et al., J Physiol 458:261-287, 1992; Jonas and Sakmann, J Physiol 455:143-171, 1992).
Gesehen am 02.05.2018